Asthma on the move: how mobile apps remediate risk for disease management. - Kenner, Alison (Health, Risk & Society)
Mobile health apps have emerged as a technological fix promising to improve asthma management. In the United States, treatment non-adherence has become the most pressing asthma risk; as such, emphasis has increasingly focused on getting asthmatics to take medications as prescribed. In this article I examine how mobile Asthma (mAsthma) apps operate as part of digital risk society, where mobile apps create new modes of risk identification and management; promise to control messy and undisciplined subjects and care practices; use algorithms to generate new risk calculations; and make risk livelier through digital assemblages. Drawing on ethnographic fieldwork, content analysis of mAsthma app design, as well as interviews with app developers, in this article I argue that these digital care technologies strip disease and risk of biographical, ecological and affective detail in ways that largely reinforce biomedical paradigms. Yet some apps offer new insight into the place-based dynamics of environmental health, a view made possible with digitised personal tracking, visual analytics and crowdsourced data. mAsthma apps are caught in the tension between the biopolitics of existing chronic care infrastructure, which reinforce a strict neoliberalised patient responsibility, and the promise of collective, place-based approaches to global environmental health problems.